2014
DOI: 10.5194/angeo-32-1-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a space-observed electric field structure for the ability to destabilize inhomogeneous energy-density-driven waves

Abstract: Abstract.We examine the effectiveness of nonuniform, quasistatic, transverse electric fields that are often observed in the auroral region in destabilization of inhomogeneous energy-density-driven (IEDD) waves. Specifically, the IEDD dispersion relation of Ganguli et al. (1985a, b) is evaluated for an electric field structure observed by the FAST satellite in the auroral ionosphere at 1000 km altitude. The background field-aligned current, plasma density and ion composition are derived from FAST observations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…The fundamental frequency of the mode increased from 0.3 f ci to f ci (black line of Figure c), resulting a broad bandwidth wave. These results are consistent with satellite observations and other laboratory experiments and suggests that electrostatic BBELF waves can be generated by IEDDI driven by the coupling of the positive and negative energy density [ Thomas et al , ; Koepke et al , , ; Bonnell et al , ; Golovchanskaya et al , , ].…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental frequency of the mode increased from 0.3 f ci to f ci (black line of Figure c), resulting a broad bandwidth wave. These results are consistent with satellite observations and other laboratory experiments and suggests that electrostatic BBELF waves can be generated by IEDDI driven by the coupling of the positive and negative energy density [ Thomas et al , ; Koepke et al , , ; Bonnell et al , ; Golovchanskaya et al , , ].…”
Section: Resultsmentioning
confidence: 99%
“…17 Note that the IEDDI solutions exist in a wide range of s, whereas CDEIC solutions (current-driven electrostatic ion cyclotron instability) degenerate for s > 0.5. 6,18 Besides, the estimates of the parallel current made from in-situ data are typically far below the excitation threshold of the CDEIC instability. 37 As shown in the present work, the inhomogeneous energy density driven instability can explain the origin of these waves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data of the FAST satellite have been used for numerical analysis of the IEDDI. 18,19 Multilayer configurations were analyzed, as proposed in Ref. 20.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it was suggested that this instability leads to formation of the broadband electrostatic turbulence [Gavrishchaka et al, 1996;Kintner et al, 2000]. In the works [Golovchanskaya et al, 2014b;Ilyasov et al, 2015;Chernyshov et al, 2015Chernyshov et al, , 2016, numerical study of the IEDD instability was performed for electrostatic ion cyclotron modes using Freja and FAST satellite data. The results of these studies verified the suggestion that the broadband electrostatic turbulence can be identified with the nonlocal electrostatic ion cyclotron mode.…”
Section: Introductionmentioning
confidence: 99%